The Transition From Intermediate School To High School: Insights From Pasifika Families - Emma Cunningham; Rebecca Jesson (Middle Grades Review, 2021)
This qualitative study examined the interplay between home and school environments across the transition from Primary School (Year 8) to High School (Year 9) for 10 high-achieving Pasifika students and their families. Interview data from the students revealed the important role that their parents played in their education. Drawings completed by the adolescents provided a high form of data illustrating the dynamic between home and school, including the influence of both on learning. Findings revealed strong intergenerational expectations for success from the dual perspectives of parent and their children, based on cultural competency and parental high expectations. The study’s results build upon existing knowledge bases which focus on parent and student strategies for success across the transition to high school, with regard to cultural competency.
Keywords: Pasifika students; transition to high school; parental involvement; academic socialization